2021
DOI: 10.1007/s12144-021-02076-w
|View full text |Cite
|
Sign up to set email alerts
|

Not a matter of quantity: quality of relationships and personal interests predict university students’ resilience to anxiety during CoViD-19.

Abstract: During the CoViD-19 pandemic, University students may have suffered from increased anxiety due to interferences in their relationships and in academic requirements, as didactic activities have moved to distance learning systems. However, being surrounded by supportive relationships and being motivated to cultivate personal interests might have decreased anxiety. In this pilot study, we collected the responses of 174 students from Italian University merit colleges to an online questionnaire, investigating their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The relationship between education and various psychological problems associated with coronavirus disease has been extensively discussed in the literature [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The most common types of fear that teachers and students may face during a pandemic are fear of family closure, fear of educational failure, and fear of losing social relationships [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between education and various psychological problems associated with coronavirus disease has been extensively discussed in the literature [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The most common types of fear that teachers and students may face during a pandemic are fear of family closure, fear of educational failure, and fear of losing social relationships [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Li and Cho et al (2021) similarly found a negative association between mathematics fear and motivation. Furthermore, Nola et al (2021) indicate that throughout the pandemic, individual interests were inversely connected to anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is crucial for adjustment to university life, and is associated with academic success and self-esteem (Conley et al, 2020 ) as well as depression (Alsubaie, Stain, Webster, & Wadman, 2019 ). Likewise, relationship difficulties, including with family and peers are the most commonly reported source of stress among students (Hurst, Baranik, & Daniel, 2013 ) and are associated with onset of depression and anxiety (Nola et al, 2021 ; Özdemir & Sağkal, 2021 ). Collectively, such social constructs can be considered as aspects of social functioning, which broadly describes an individual's ability to participate in society and their satisfaction with their social roles (Burns & Patrick, 2007 ).…”
Section: Introductionmentioning
confidence: 99%